Mechanical spectroscopy: some applications to material science. (5th April 2006) - Pelletier, J.M.; Gauthier, C.; Chazeau, L.
Mechanical spectroscopy is a powerful tool for the study of materials. In particular, it is shown that such a technique can help the characterisation of amorphous materials, whatever their nature (polymer, ceramic or metal). It also provides precious information for the understanding of the mechanical relaxations involved in the deformation of these materials. This technique is also useful for the study of semi-crystalline material, their crystallisation process, and when they are filled, the influence of the fillers on this phenomenon. However, through the discussion, it is evidenced that, to provide insightful results, this technique must always be used in parallel with other techniques such as DSC, techniques of microstructural characterisation or mechanical modelling.